Design and Control of an Automotive Variable Hydraulic Damper Using Cuckoo Search Optimized Pid Method - Zhao, Jing; Wong, Pak Kin; Xie, Zhengchao; Ma, Xinbo; Hua, Xingqi (International journal of automotive technology, 2019)
The semi-active suspension (SAS) system has been one of the most attractive topics due to its simplicity and effectiveness in the control of vehicle dynamics. This research proposes a cuckoo search optimized proportional-integral-derivative (CS-PID) strategy for the damping force control of the semi-acive suspension system in order to improve vehicle ride quality. Firstly, a quarter-car suspension model with air spring and variable hydraulic damper (VHD) is developed. By constructing the detailed analytical model and describing the working process, the regulating mechanism and external characteristics of the VHD are presented. Subsequently, the CS-PID strategy is designed to generate the desired damping force according to the vehicle states in real-time, followed with the evaluation of the proposed strategy. Finally, the experimental tests are carried out to verify the accuracy of the VHD model and examine the feasibility of the proposed strategy. The numerical simulation reveal that the proposed control strategy is effective in improving the vehicle performance and the experimental results show that the CS-PID strategy can be successfully implemented in the suspension system for practical use.